Oral Health Status among Tobacco Users of Selected Rural Population (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Tobacco smoking is a major risk factor for the development of oral cancer in developing countries. The prevalence of tobacco use is the highest amongst poor people of low educational background. Cancer of oral cavity is the commonest cancer in our country and ranked 5th among male and 4th in female.Objectives: To assess the oral health status among tobacco users in a selected rural population of Dhamrai and Saturia Upazilla in Dhaka district.Materials and Methods: This descriptive cross sectional study was conducted from 1st November 2018 to 15th January 2019. Non-probability purposive sampling was done and data was collected from 445 respondents.Results: Among the respondents, 26% were day laborer and 24% were businessmen with family income were between Tk 5000-Tk 10000. About 78.65% of the respondents have tobacco smoking habit among them 75% had current tobacco chewing habit as jarda. 69.21% of the respondents did not complain of any oral problems. Oral health status among the current tobacco smokers and chewers showed that they had dental stain (90.78%), dental plaque (65.17%), dental calculus (44.49%), dental carries (53.03%), bad breathing smell (75%), soft tissue inflammation (23.82%), loose teeth (26.74%) and ulceration (8.54%) in their oral cavity.Conclusion: Tobacco control protects the rights and health of non-smokers, specially babies, children, youth and pregnant women. The dangers posed to oral health from smoking and chewing tobacco are well documented but the lack of knowledge of the risks is a concern. So oral health should be given great importance from childhood and dental checkup should be done regularly. The general people should be made aware of it through various mass media.Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 144-147